A Density-Based Ramp Metering Model Considering Multilane Context in Urban Expressways. (2nd March 2017) - Tang, Li; Luo, Xia; Zhai, Pengfei; Gao, Xunfei
Abstract : As one of the most effective intelligent transportation strategies, ramp metering is regularly discussed and applied all over the world. The classic ramp metering algorithm ALINEA dominates in practical applications due to its advantages in stabilizing traffic flow at a high throughput level. Although ALINEA chooses the traffic occupancy as the optimization parameter, the classic traffic flow variables (density, traffic volume, and travel speed) may be easier obtained and understood by operators in practice. This paper presents a density-based ramp metering model for multilane context (MDB-RM) on urban expressways. The field data of traffic flow parameters is collected in Chengdu, China. A dynamic density model for multilane condition is developed. An error function represented by multilane dynamic density is introduced to adjust the different usage between lanes. By minimizing the error function, the density of mainstream traffic can stabilize at the set value, while realizing the maximum decrease of on-ramp queues. Also, VISSIM Component Object Model of Application Programming Interface is used for comparison of the MDB-RM model with a noncontrol, ALINEA, and density-based model, respectively. The simulation results indicate that the MDB-RM model is capable of achieving a comprehensive optimal result from both sides of the mainstream and on-ramp.